Superelastic pendulum isolator with multi-stage variable curvature for seismic resilience enhancement of cold-regional bridges. (1st June 2023) - Zheng, Wenzhi; Tan, Ping; Li, Jian; Wang, Hao; Liu, Yanhui; Xian, Zhibin
Highlights: A novel superelastic pendulum isolator with multi-stage variable curvature (SPIVC) is developed to enhance cold-regional bridge resilience. A cost-effective design method is developed to optimize the parameters of the SPIVC system. The seismic resilience of the bridges is systematically investigated considering cold-regional ambient temperature effects. Several case studies are conducted to demonstrate the effectiveness of the SPIVC equipped with CuSMA for cold-regional bridges. Optimum resilience enhancement of cold-regional bridges is achieved using SPIVC system under near-fault earthquakes. Abstract: This study develops a novel superelastic pendulum isolator with multi-stage variable curvature (SPIVC) to enhance the seismic resilience of the cold-regional bridges. The SPIVC comprises the improved conical friction pendulum bearing (CFPB) with flat surface, spherical surface and inclined surface connected in series and re-centering devices fabricated by copper-based shape memory alloy (CuSMA). The novel SPIVC features the deformation accommodation under service loadings and seismic isolation under seismic shaking. The numerical model of the SPIVC is developed within OpenSees using the experimentally observed parameters. A typical continuous bridge is selected as benchmark bridge to investigate the seismic performance of the SPIVC system in cold regions. To achieve optimum parameters of the SPIVC, a cost-effective design method is developed based on the hysteretic characteristics of the re-centering device. The seismic performance of cold-regional bridge with SPIVCs under near-fault earthquakes is investigated and assessed by case study. Results show that the proposed method is effective to capture the isolator parameters. Case studies demonstrate the re-centering and seismic isolation performance of the SPIVC system employing the optimum parameters for bridges in cold regions, i.e., the novel SPIVC system can perform the dual control of the girder displacement, permanent isolator displacement and the seismic shear of the piers for each ambient temperature. The achieved findings can be employed to guide the resilience enhancement of the cold-regional structures and potential seismic applications.